The multifaceted nature of participation motivation in elite Canadian women Rugby Union players - Kerr, J. H. (International Journal of Sport and Exercise Psychology, 2021)
This study examined the nature of participation motivation for starting and continuing to play rugby among elite Canadian women rugby union players. A snowball technique was used to generate a sample of 10 international elite-level Canadian women rugby players who took part in open-ended, semi-structured interviews. An inductive thematic qualitative approach was used in the data analysis and reversal theory was used in the interpretation of interview data. The qualitative research methods provided detailed information about participation motivation. Players` rugby experiences were generally positive. Four major participation motivation themes comprised of seven sub-themes were identified. These were: Getting started with rugby; Physical aspects (physicality and aggression; physical challenge); Achievement and success (learning a new sport; sport suitable for my body type); and On- and off-field player interaction (teammates/team environment; friendship and rugby community; being non-conformist).